The Effect Of Strategic HRM On Competitive Advantage Including The Mediating Impact Of Intangible And Tangible Firm Performance - Mohammed, Mhsen Alwan; Kadhim, Rabab Ibrahim; fadel, Khariya abed (The journal of contemporary issues in business and government, 2021)
A competitive advantage (CA) would no longer be the company's physical properties but the people's non-physical resources. This study designed to mediate the impact of HRM Strategic Practices on CA on the transcendent corporate performance and actual business performance. Erbil was in Kurdistan, Iraq, from four cities. Questionnaires sent to the seven companies selected. The path control strategy for analysis used this research to model the collected data on partly small and structural equations (PLS-SEM). The evaluation results from the Construct show that the measurements of the SHRMP, IFP, TFP, and CA range from 0.60-0.92. There is still a variable loading value of 0.50 to 0.60, although some authors propose loads of factor greater than 0.70. We have maintained and accepted the limitations given the preceding for further analysis. For SHRMP, IFP, TFP and CA, the average of the latent variables were 0.56, 0.51, 0.58 and 0.51, respectively. The obtained AVE values were coherent. Our results demonstrate that each structure is more comprehensive than its square correlations with the diagonal and adventurous Square Roots AVE. In this research, HRM strategy and competitive advantages, particularly in Iraq, are linked to the company's metaphysical and factual mediator role. The study results offer innovative views. This research has also determined the importance of corporate (public/private) types. Our results show that the intangible performance of the employees and tangible results play a crucial role in securing competitive, sustainable benefits for firms in Iraq.